How is the likelihood of fire sales in a crisis affected by the interaction of various bank regulations? - Kirti, Divya (IMF Working Papers; Working Paper ;, 2017)
We present a model that describes how different types of bank regulation can interact to affect the likelihood of fire sales in a crisis. In our model, risk shifting motives drive how banks recapitalize following a negative shock, leading banks to concentrate their portfolios. Regulation affects the likelihood of fire sales by giving banks the incentive to sell certain assets and retain others. Ex-post incentives from high risk weights and the interaction of capital and liquidity requirements can make fire sales more likely. Time-varying risk weights may be an effective tool to prevent fire sales.